THE INFLUENCE OF BRAND AMBASSADORS, LIFESTYLE AND CUSTOMER SATISFACTION ON CONSUMER BUYING INTEREST IN SCARLETT WHITENING PRODUCTS IN BATAM CITY - Siregar, Anita; Hikmah, Hikmah (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
Through digital-based marketing such as marketing through Instagram media or online sales platforms such as Shopee and Sociolla, customers can easily buy products, see, review usage and companies can also take advantage of digital-based marketing to attract customers. This research was conducted for this purpose of knowing the effect of brand ambassadors, lifestyle and customer satisfaction on consumer purchase intention in Scarlett Whitening products in Batam City.  The sample used in this study used the Jacob Cohen formula, the number of respondents was 204 respondents and applied non-probability sampling techniques. The comes aproximately of the bear in mind seem that patron achievement has an effect of twenty-5 factor 0 percentage on purchase puposefulin. In the interim, the comes about of theory testing appear that brand ministers, lifestyle and customer satisfaction partially and collectively exert a good and prominent impact on consumer purchase intention in Scarlett Whitening products in Batam City.